Job Redesign, Automation, and Digital Workforce Competencies in the Twenty-First Century - Darmawan, Didit (Metromedia, 2025)
This study investigates the future of work in the era of artificial intelligence and automation, focusing on implications for job design and digital labor management within human resource management (HRM). Using a qualitative literature review from the past two decades, it synthesizes insights on job redesign, hybrid arrangements, gig work, and remote work. Thematic analysis reveals two central areas, the restructuring of work under AI adoption and the development of future competency frameworks. Findings indicate that automation must be integrated with job design, as task allocation between humans and AI affects workload, learning, and work relationship quality. HRM should act as a strategic partner from the early design stage, utilizing analytics, communication strategies, and manager development to effectively manage a hybrid workforce. The study underscores the need for hybrid competency profiles combining digital proficiency, analytical skills, socioemotional intelligence, and self-management. Employability and dynamic capabilities highlight the necessity of lifelong learning and adaptability. Theoretically, this research contributes to understanding how AI shapes work structures and competency demands. Practically, it guides organizations in redesigning jobs, developing digital workforce competencies, and fostering adaptive learning ecosystems. Collaboration among HR, business leaders, and technology developers is essential to reduce competency gaps and mitigate resistance to technological change.